2022
DOI: 10.1111/bph.15973
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid 1 (CB1) receptor arrestin subtype‐selectivity and phosphorylation dependence

Abstract: Background and purpose Arrestin or G protein bias may be desirable for novel cannabinoid therapeutics. Arrestin‐2 and arrestin‐3 translocation to CB1 receptor have been suggested to mediate different functions that may be exploited with biased ligands. Here, the requirement of a recently described phosphorylation motif ‘pxxp’ (where ‘p’ denotes phosphorylatable serine or threonine and ‘x’ denotes any other amino acid) within the CB1 receptor C‐terminus for interaction with different arrestin subtypes was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
(97 reference statements)
2
8
0
Order By: Relevance
“…It has been reported that CB1R agonists have lower potencies for β-arrestin recruitment compared to G protein coupling . As expected, most of the agonists tested in this study demonstrated ∼3-fold weaker potencies for β-arrestin 2 recruitment than for G i1 engagement (Figure and Table ).…”
Section: Resultssupporting
confidence: 78%
“…It has been reported that CB1R agonists have lower potencies for β-arrestin recruitment compared to G protein coupling . As expected, most of the agonists tested in this study demonstrated ∼3-fold weaker potencies for β-arrestin 2 recruitment than for G i1 engagement (Figure and Table ).…”
Section: Resultssupporting
confidence: 78%
“…Altogether, at CB 2 , our data yielded a potency rank order of ADB > MDMB > MMB ∼ MPP > AB > CUMYL > APP. This was not entirely in line with the MPA assay, with as a notable difference the CUMYL-bearing HEXINACA compound (44), which conferred the best potency in the MPA format, while being the second worst in the βarr2 assay, although was still highly potent (<10 nM). However, with the exception of the less active APP-HEXINACA (40), the differences in potency at CB 2 between the other headgroup-bearing HEXINACA compounds were overall relatively limited, in both assay formats.…”
Section: Initial Evaluation Of Compounds 5 and 25−65 Via A β-Arrestin2mentioning
confidence: 93%
“…While WIN55,212−2 is not an indazole-3-carboxamide like MDMB-FUBINACA, it bears the highest similarity to our investigated compounds, compared to other published CB 2 -agonist structures. Eight ligands were selected for docking: ADB-HEXINACA (5), MDMB-HEXINACA (42), MDMB-5en-HEXINACA (49), MDMB-HEXICA (29), MDMB-HEX7AICA (56), ADB-5en-HEXINACA (46), MPP-HEXINACA (43), and CUMYL-HEXINACA (44), providing a varied subset of compounds to assess the impact of head, core, and tail combinations. It was generally observed that at CB 1 , the ligands' calculated binding poses were equivalent to that of the cognate ligand MDMB-FUBINACA (Figure 7a).…”
Section: Initial Evaluation Of Compounds 5 and 25−65 Via A β-Arrestin2mentioning
confidence: 99%
See 2 more Smart Citations